Evaluation of the pedagogical model used in virtual reality simulations for training portuguese firefighters - Reis, Vitor (2021)
This paper details the pedagogical model used in virtual reality simulations for training Portuguese fire officers in emergency operations management and the evaluation of students about the implementation of the model throughout the training courses. The data of this quantitative study were collected over two years (2018-2019) and involved the participation of 89 fire officers from all over the country, who attended 12 training courses delivered at the Portuguese National Fire Service School (Escola Nacional de Bombeiros). Each course included seven to eight students, all experienced incident commanders with at least five years of service in the role. Every student played as incident commander in two different virtual reality training scenarios and their performance was assessed using a standardized evaluation tool. Students evaluated the pedagogical model implementation in virtual reality simulations through a questionnaire applied at the end of each course. The study’s conclusions point out that most students consider the pedagogical model successfully implemented.